2020
DOI: 10.1177/2329488420976805
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Workplace Inclusion on Employee Assimilation Outcomes

Abstract: This study investigates the relationship between coworker inclusion and assimilation outcomes. To begin, this paper reviews components of assimilation and inclusion that are thought to co-occur in the workplace. In addition, employees of a large university in the Pacific Northwest were surveyed electronically to investigate the extent to which inclusion and assimilation outcomes are related. Finally, a discussion is offered that details the study’s findings, that is, task- and social-based aspects of inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…Singh et al ., 2018) and because it promotes general feelings of workplace inclusion (e.g. Redding and Sincoff, 1984; see also Miller and Manata, 2023). Support from others in the workplace is also likely to come in the form of aiding with task accomplishment (Marks et al ., 2001), which is also expected to bolster performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Singh et al ., 2018) and because it promotes general feelings of workplace inclusion (e.g. Redding and Sincoff, 1984; see also Miller and Manata, 2023). Support from others in the workplace is also likely to come in the form of aiding with task accomplishment (Marks et al ., 2001), which is also expected to bolster performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Task and social-based aspects of inclusion (i.e. task inclusion and social inclusion) are found to be positively related to assimilation outcomes (Miller and Manata, 2020). Assimilation outcomes refer to results from the process in which organizational members integrate into the organization system by individualizing their roles (Myers and Oetzel, 2003).…”
Section: Inclusion Measurements and Initial Empirical Findingsmentioning
confidence: 99%
“…Yet, research indicates that only 11% of companies truly understand what inclusion is, could define it or understand its impact in workplaces (Mondal, 2021). Moreover, several studies have shown complexities in individual feelings of being included and the inclusion process, which may entail assimilation outcomes (Miller and Manata, 2020), a lack of sense of self (Ortlieb et al , 2021) and intricacies of “hybridity” (Dobusch, 2014). These complexities and contradictions with the dominant discourse of positivity in inclusion suggest the need for understanding inclusion in a more critical way.…”
Section: Introductionmentioning
confidence: 99%
“…Greater inclusion has the capacity to elevate quality of work life for non-dominant group members, which in turn grows diversity through attracting a wide range of applicants. Just as significant, inclusion of these multiple voices has a positive and significant link to creativity (Lauring & Klitmøller, 2017) as well as financial and performance outcomes (Cascio et al, 2019;Hirak et al, 2012;Miller & Manata, 2020).…”
mentioning
confidence: 99%
“…Fortunately, effective socialization and assimilation practices counteract these risks. To this effect, Miller and Manata (2020) shed rich light on the vital role of communication in worker assimilation. Fostering inclusion at this stage becomes important for long-term retention and developing a broader culture of openness and diversity throughout an organization.…”
mentioning
confidence: 99%